Faunistic accounts on aphids (Homoptera Aphidoidea) of central-eastern Italy (Bollettino di zoologia agraria e bachicoltura, 2024)
Biological, ecological and taxonomical accounts on the aphid fauna of the two Italian administrative Regions Abruzzo and Molise are given. An amount of 364 species and subspecies of aphids were collected, which correspond to 47% of the Italian aphid fauna, being the latter presently composed by 776 species altogether. In the Region Abruzzo, 347 out of the 364 taxa were detected, of which 178 were collected inside the National Park protected area. An apparently less rich aphid fauna composition is present in the Region Molise, where only 245 species were detected. Fifteen taxa of specific or subspecific level, among all those ones collected in the two Regions, are here recorded for the first time as component of the Italian aphid fauna. As concern the systematic relationships, the 364 species collected belong to 17 out of the 19 groups of families and subfarnilies into which the ltalian aphids can be subdivided. A short biogeographical discussion points out that a large proportion of species (about 61% altogether) shows a wide distribution (cosmopolitan, holarctic and palaearctic species), whereas 38% of species have an European (34%) or Mediterranean (4%) distribution. Comparing to a similar classification into chorological categories of all the Italian aphids, there is in Abruzzo-Molise an apparent higher percentage (about 13%) of species belonging to categories of wider geographical distribution; this suggests that a number of aphids likely remain still to be detected in the two Regions.
Keywords: aphids; fauna; taxonomy; Abruzzo & Molise regions; Italy